KERANGKA KONSEPSIONAL PEMBINAAN PROFESIONALISME GURU MELALUI SUPERVISI PENDIDIKAN - Nelly Izmi (El-Rusyd, 2019)
Educational supervision is needed to overcome various educational and teaching issues that are often complained by the community such as the lack of teachers ability to overcome difficulties in preparing teaching documents, teachers difficulties in carrying out teaching tasks using skills of teaching according to the demands of learning materials, lack of coordination between colleague, less effective of learning strategies and so on. However, the implementation of educational supervision is not easy to do if the teacher consider that the supervision done by the headmaster identified with the evaluation so that the teacher in facing it becomes worried, as if the headmaster is looking for weakness of the teacher. The method used in this study is library research, a study that uses the main reference and support (primary and secondary sources). The discussion used in the writing using inductive, deductive and comparative analysis. The results showed that educational supervision contains several main activities, namely continuous coaching, improvement of teaching and learning situation with the ultimate goal of achieving educational goals and the growth of learners. In other words, the educational supervision is a service process to help and nurture the teachers in order to improve professionalism.